VARIASI ISOLEK MELAYU DI SUMATERA SELATAN - Muhammad Irsan (Madah: Jurnal Bahasa dan Sastra, 2015)
This study discusses the variation of Malay isolects in South Sumatra dealing with phonological and lexical variation. This sudy used diachronic dialectology approach. The data were gathered by the method of conversation with interview techniques using the questionnaires of Research on Cognates and Mapping of Regional Language in Indonesia.The interview was conducted on informants from 21 villages. The vocabulary evidences are described in the form of sound variations and correspondences as well as the types of sound changes based on the framework as performed by Lehman, Hock, and Crowley. Dialectometry and lexicostatistics were used to determine the status of language and cognates between the isolects. The research findings showed that there were phonological and lexical correspondences in vocals and consonants. Sound variations found in this study were caused by morphophonemic and nasalization processes. Sound changes in the form of metathesis, mergers, epenthesis, aphaeresis, syncope, and apocope were also found along with Van der Tuuk correspondence rules in the form of sound variation r~l, d~l and other variations, such as l~t, h~l, d~n, and h~s. The sound correspondences and variations showed the riches of dialectal variation as a characteristic of Malay isolects in South Sumatra, which derived from the same language, i.e. the Malay. The result of lexicostatistics and dialectometry analysis strengthened the interdialect cognates and the same language status between the isolects.